Vpliv ekonomskega pristopa na presojo vezanih in paketnih prodaj v konkurenčnem pravu EU - Repas, Martina (LeXonomica, 2021)
Influence of economic principles on tying and bundling in EU Competition Law. Article deals with tying and bundling in the light of abuse of dominant position, which is prohibited under Article 102 of the Treaty on the Functioning of European Union. These practices generally refer to joint sale of distinct (independent) products not belonging to the same product market and are quite frequent. However, they can be problematic if the undertaking using these practices has a certain degree of market power. According to economic theory, tying and bundling creates pro-competitive and anticompetitive effects. Therefore, per se illegality approach is not appropriate without in-depth analysis of effects on competition, although the analysis of classical tying cases decided by the Commission and the Court of Justice of the European Union do not point in this direction. In this regard, article reviews development in treating of tying and bundling in competition law of EU and USA, which shifted from per se illegality approach to the approach that emphasizes actual and potential economic effects of allegedly illegal practice and not form. This approach can be found in the case Microsoft v Commission. It is also accepted in the European Commission's Guidance on its enforcement priorities in applying Article 82 (EC) to abusive exclusionary conduct by dominant undertakings.Povzetek. Prispevek obravnava vezano in paketno prodajo v luči zlorabe prevladujočega položaja, ki je prepovedana po členu 102. Pogodbe o delovanju Evropske unije. Tovrstne prodaje splošno pomenijo skupno prodajo samostojnih oz. ločenih proizvodov, ki praviloma ne sodijo na isti proizvodni trg, in so v praksi precej pogostne, čeprav so problematične le v primeru, ko ima podjetje, ki se teh praks poslužuje, določeno stopnjo tržne moči. V skladu z ekonomsko teorijo vezane in paketne prodaje nedvomno ustvarjajo protikonkurenčne učinke. Zato pristop, po katerem bi se tovrstne prodaje obravnavale kot per se nezakonite brez natančne analize učinkov na konkurenco, ni na mestu, čeprav analiza klasičnih primerov vezanih poslov, ki sta jih obravnavale Komisija in Sodišče, ne kažeta tako. Prispevek v zvezi s tem prikaže razvoj obravnavanja vezanih in paketnih prodaj v konkurenčnem pravu EU in ZDA, ki se je od zastopanja per se stališča preusmeril k pristopu, ki poudarja dejanske ali pričakovane ekonomske učinke domnevno nezakonitega ravnanja. Ta pristop se v EU kaže v zadevi Microsoft proti Komisiji, sprejet pa je tudi v Navodilih Komisije glede prednostnih nalog izvrševanja pri uporabi člena 82 Pogodbe ES za izključevalna ravnanja.